Exploring ESP Students’ Preferences for Oral Corrective Feedback - Roro Millatu Al Ghaniy (Tell : Teaching of English Language and Literature Journal, 2025)
Although some researchers show negative views toward oral corrective feedback, many believe that oral corrective feedback is beneficial for correcting the students’ errors and improving their speaking skills. This survey study aims at investigating ESP students’ oral corrective feedback preferences in speaking class. One hundred and sixty-five students from different study programs participated in the study. Moreover, a closed-ended questionnaire was employed to collect the data. The results revealed that the students strongly wanted their lecturers to fix their spoken errors. The students also showed their favorable attitude toward overall error corrections given by the lecturers instead of peers. Concerning the types of errors, a huge number of the students either agree or disagree toward oral correction on grammatical errors, pronunciation errors, and inappropriate vocabulary usage and expressions. Additionally, explicit correction was the most favorable feedback among the students followed by elicitation and metalinguistic feedback. Exploring students’ preferences of oral corrective feedback assists lecturers to find the most effective way of delivering feedback that suits the students’ needs. By implementing the effective feedback, not only students’ errors can be corrected but their speaking skills can be improved. Keywords: oral corrective feedback preferences; ESP-speaking course